Proposta e relato de intervenção lúdico-odontológica em crianças de 2 a 6 anos de uma creche na cidade de Lençóis Paulista-SP - Perantoni, Viviane Ugucione (2009)
Health education as a social practice aimed at the collective, represents an important opportunity to expand the performance practices of oral health promotion. Many preventive measures to combat air cavity (most common in children) and periodontal disease ailments that most affect the oral cavity. Accordingly, the present study was to a proposal for intervention recreational / dental care in children 2 to 6 years in a nursery in the town of linen Paulista, SP. We studied 63 children attending the nursery Ocas Organization (Christian Social Action), which were subjected to standardized oral examinations before and after an intervention in oral health education using a variety of recreational activities such as games, painting, opera and more. The choice of this method promotes integralizing action, and this strategy has reached the whole community as the leading school information important to their families. The parameter we used the DMF-T index, appropriate to show in general the oral health condition of an individual. The proposed intervention showed a marked decrease in the DMF-T both in the general group and in stratified analysis in some age groups. It is concluded that there was a significant reduction in the DMF-T, but we believe that the linkage between this activity and reduced novelty informative health education requires additional parameters, considering that oral health is multifactorial.